Measurement Scales of Suicidal Ideation and Attitudes: A Systematic Review Article - Parvin Ghasemi; Abdolreza Shaghaghi; Hamid Allahverdipour (Tabriz University of Medical Sciences, 2015)
Background: The main aim of this study was to accumulate research evidence that introduce validated scales to measure suicidal attitudes and ideation and provide an empirical framework for adopting a relevant assessment tool in studies on suicide and suicidal behaviors. Methods: Medical Subject Headings' (MeSH) terms were used to search Ovid Medline, PROQUEST, Wiley online library, Science Direct and PubMed for the published articles in English that reported application of an scale to measure suicidal attitudes and ideation from January 1974 onward. Results: Fourteen suicidal attitude scale and 15 scales for assessing suicidal ideation were identified in this systematic review. No gold standard approach was recognized to study suicide related attitudes and ideations. Conclusion: Special focus on generally agreed dimensions of suicidal ideation and attitudes and cross-cultural validation of the introduced scales to be applicable in different ethnic and socially diverse populations could be a promising area of research for scholars.